Pendampingan Pembuatan NIB Berbasis OSS Untuk Meningkatkan Pemahaman Legalitas dan Kesejahteraan UMKM di Desa Mojopuro, Jatiroto, Wonogiri - Eka Nia Wulandari; Muhamad Azka Ziyan Naufan; Bilqis Naufi (Yayasan Daarul Huda Kruengmane, 2025)
The assistance program for the creation of the Business Identification Number (Nomor Induk Berusaha / NIB) through the Online Single Submission (OSS) system in Mojopuro Village, Jatiroto District, Wonogiri Regency, was implemented as an effort to improve community understanding of the importance of business legality while encouraging the independence of Micro, Small, and Medium Enterprises (MSMEs). The method used in this activity was a qualitative approach with descriptive techniques. The program was conducted in two stages: socialization and outreach at the Mojopuro Village Hall, followed by direct assistance at the community service post. The results showed an increase in business actors’ understanding of the benefits of NIB, the ease of the OSS registration process, and legal awareness regarding business legality. A total of 26 MSMEs successfully obtained official NIBs. This program also encouraged the village government to commit to continuing the assistance activities independently. Thus, assistance in NIB registration not only enhances business legality but also strengthens economic empowerment and sustainable digital literacy within the rural community.